A Brief to the Commission for the Estates General on Education from Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1995)
One of the stated aims of the Home and School movement is to assist in forming public opinion favourable to educational reform and to the advancement of the education of the child. Thus we are pleased to be able to submit this brief to the Commission for the Estates General on Education. This brief is presented in both French and English. However, these two versions are not direct translations, but have been written independently based on the same input and the same discussions. Care has been taken to examine both versions to ensure that their message is the same.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1989)

A Report to Superior Council of Education on the State and Needs of Education in 1985 from Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1985)
Quebec Federation of Home and School Associations (QFHSA), founded in 1944 is an independent voluntary parental organization representing approximately six thousand families, mainly within the English speaking communities throughout the province. Parent volunteers are active within local Home and School associations, the national level through the Canadian Home and School Parent Teacher Federation. One of the stated aims of the Home and School movement is to assist in forming public opinion favourable to reform and the advancement of the education of the child. thus we are pleased to submit this report on the state and needs of education as requested by the Superior Council of Education.

A Statement from Quebec Federation of Home and School Associations to the Superior Council of Education on the State of the Condition of Teaching in the Province of Quebec - Quebec Federation of Home and School Associations (QFHSA) (1984)
Quebec Federation of Home and School Associations (QFHSA) is a parent group, working as volunteers at the school, provincial and national levels. QFHSA takes particular pride in the fact, that over the last forty years, parents, as volunteers, have seconded the schools' efforts to provide assistance in areas of school life, to upgrade or enhance the school's environment and, thereby, benefit the students. As an adjunct to direct involvement at the school level, though its resolutions addressed, over the years, to various levels involved in the educational process, QFHSA has pinpointed areas its members felt needed either more funding, changing, support, introduction, etc., as the case may be. These will be referred to specifically later on.

Brief to the Minister of Education Regarding the Cumulative School Record Presented by Quebec Federation of Home & School Associations - Quebec Federation of Home and School Associations (QFHSA) (1974)
The Quebec Federation of Home & School Associations, representing over 12,000 families who are members of local associations in schools or groups of schools, in preparing this Brief has received comments and assistance from associations on the Island of Montreal, the south and north shore , Quebec City, Hull, Gaspe and the Eastern Townships and also from a number of school committees .

Brief on Teacher Classification Presented by Quebec Federation of Home & School Associations to Commission of Study on the Classification of Teachers - Quebec Federation of Home and School Associations (QFHSA) (1974)
The Quebec Federation of Home & School Associations at its Annual General Meeting held in May 1971, passed two resolutions on the issue and conflict arising in respect of Teacher Classification to be directed to the Minister of Education.

Brief on Bill 62 to the Education Committee of the National Assembly of the Province of Quebec - Quebec Federation of Home and School Associations (QFHSA) (1970)
The Quebec Federation of Home and School Associations, formerly the Quebec Federation of Protestant Home and School Associations (hereinafter referred to as "Quebec Federation") wishes to present the Education Committee of the National Assembly of the Province of Quebec with the views of its membership on the proposed Bill 62.